UNLOCKING IMPULSIVE PURCHASING: THE INFLUENCE OF FREE SHIPPING TAGLINES AND ONLINE CUSTOMER REVIEWS ON SHOPEE SHOPPERS - Azis Muthalib, Dzulfikri (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
This study aims to examine the influence of the